The need to reflect language change in ELT sources. (14th June 2016) - Booth, John E.
Abstract: This is a feature in which individuals are invited to express their personal, and sometimes controversial, views on professional issues. These views are not necessarily those of the Editor, the Editorial Panel, or the Publisher. Reaction to Comment features is welcome in the form of a letter to the Editor or a Readers Respond article.